2019
DOI: 10.1051/0004-6361/201936162
|View full text |Cite
|
Sign up to set email alerts
|

Properties of central stars of planetary nebulae with distances in Gaia DR2

Abstract: Context. We have compiled a catalogue of central stars of planetary nebulae (CSPN) with reliable distances and positions obtained from Gaia Data Release 2 (DR2) astrometry. Distances derived from parallaxes allow us to analyse the galactic distribution and estimate other parameters such as sizes, kinematical ages, bolometric magnitudes, and luminosities. Aims. Our objective is to analyse the information regarding distances together with other available literature data about photometric properties, nebular kine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 47 publications
2
20
0
Order By: Relevance
“…If we compare our distance estimations results with those derived by other authors (see [1] for details), we appreciate a significant agreement with those obtained from astrometric methods (USNO and HST). On the other hand, we found that distances obtained from non-LTE model fitting are in most cases overestimated and would need to be carefully reviewed.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…If we compare our distance estimations results with those derived by other authors (see [1] for details), we appreciate a significant agreement with those obtained from astrometric methods (USNO and HST). On the other hand, we found that distances obtained from non-LTE model fitting are in most cases overestimated and would need to be carefully reviewed.…”
Section: Discussionsupporting
confidence: 84%
“…Considering physical radii and observational expansion velocities taken from the literature, we derived the so-called kinematical ages of the nebulae. Although most of the PNe are rather young, with ages under 15,000 yr, we also found nebulae spanning ages well beyond those values (see [1] for details). From the average kinematical age value and the mean physical radius of the sample, we obtained a value for the visibility time (i.e., the amount of time elapsed since the PN was created) of the PNe population, < T VT >, similar to that derived by Jacob et al [5].…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations